Program For Educational Qualification Diploma French students/ teachers Based on competences Case study : Diploma French students/ teachers Based, Damascus University Faculty of Education (Damascus University Journal of educational and Psychologyical sciences, 2024)
This study aimed  at Developing a training program Based on competences the Educational Qualification Diploma Frenchstudents/teachers in educational Qualification DiplomaFor Developing Theircompetences .                                                                   -The study applied on an experimental group of (30) male and female students ofEducational Qualification Diploma at the faculty of Education/Damascus University.                                            Research findings:                                                                            The findings in all aspects of the study showed a clear effect of the suggested training program in increasing the competences of the students/teachers necessary for teaching, by comparing the arithmetic means scores and T value, the ratio of the statistical indication of the sample (experimental and controlling) on the  Achievement test measured through the theoretical and performance test measured by using the checklist which was used to observe the scores of the female students/ teachers (study sample) which belong to the interest of the experimental sample,   The adoption of  training programs prepared on the basis of educational competences in the pre-service training of teachers. The implementation of such program has significantly indicated a clear improvement of the trainees' performan cecompetences .
Keywords: Educational Competences; Teaching Methods Of French; Students/Teachers In Educational Qualification Diploma; Training Program